MEREFLEKSIKAN TEORI PEMASARAN KE DALAM PRAKTIK PEMASARAN SYARIAH - Tamamudin (Jurnal Hukum Islam, 2014)
Marketing has undergone rapid development since the 1990s. Until now, marketing is not only known as a practical element but marketing is also known as one of the disciplines. In other words, marketing has elements of the scientific method that can produce marketing theories. However, marketing does not have a general theory that can explain all aspects related to marketing itself. The fact that marketing continues to play an important role in corporate strategy in several companies indicate that there is an opportunity and take a real approach to build marketing competence as a source of competitive advantage. Business practices and marketing today is experiencing a shift or a transformation from an intellectual level (rational), to the emotional, spiritual, and finally to. On the intellectual level (rational), marketers will address the functional-technical marketing by using a number of marketing variables that exist, such as the marketing mix (marketing mix), market segmentation, targeting, branding, positioning.